Perspectives on Conservation Impacts of the Global Primate Trade - Gal Badihi; Daniel R. K. Nielsen; Paul A. Garber; Mike Gill; Lisa Jones-Engel; Angela M. Maldonado; Kerry M. Dore; Jennifer D. Cramer; Susan Lappan; Francine Dolins; Emerson Y. Sy; Agustin Fuentes; et al. (International Journal of Primatology, 2024)
The global trade in nonhuman primates represents a substantial threat to ecosystem health, human health, and primate conservation worldwide. Most of the primate trade involves trade for pet-keeping, consumption, or biomedical experimentation. We present an overview of international primate trade through five case studies; each describes a different facet of this trade. We draw on published scientific literature, media outlets, and open access datasets, including the CITES Trade Database to build these case studies. Case study 1 describes the role of introduced island populations of Macaca and Chlorocebus in trade for biomedical experimentation; case study 2 covers the global health threats posed by the primate trade, including zoonotic disease transmission once animals enter the trade pipeline; case study 3 addresses the ways that changing patterns of primate trade, from local markets to online, have increased the demand for primates as pets; case study 4 recognizes the role that local environmental activism can play in mitigating trade; and case study 5 shows variation between global regions in their contribution to the primate trade. We recommend greater oversight of primate trade, especially domestic trade within primate range countries, and real-time reporting to CITES to accurately track primate trade. Effective conservation-focused regulations that can minimise the negative effects of primate trade must be tailored to specific regions and species and require transparency, careful regulation, field research, and an understanding of the magnitude of this trade.

The importance of the seafood processing sector to coastal community resilience - Lori A. Cramer; Jennifer Beaullieu; Jamie Doyle; Marta Maldonado; Hillary Egna; Maria Johnson; Flaxen D.L. Conway (Marine Policy, 2023)

Public Values and Attitudes toward Marine Reserves and Marine Wilderness - Jennifer R. Johnston; Mark D. Needham; Lori A. Cramer; Thomas C. Swearingen (Coastal Management, 2020)

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A comparison of adult body size between captive and wild vervet monkeys (Chlorocebus aethiops sabaeus) on the island of St. Kitts - Trudy R. Turner; Jennifer Danzy Cramer; Alexis Nisbett; J. Patrick Gray (Primates, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Population admixture modulates risk for alcohol dependence - Lingjun Zuo; Xingguang Luo; Jennifer B. Listman; Henry R. Kranzler; Shuang Wang; Raymond F. Anton; Hilary P. Blumberg; Murray B. Stein; Godfrey D. Pearlson; Jonathan Covault; Dennis S. Charney; Daniel P. van Kammen; et al. (Human Genetics, 2009)

The effects of beta-alanine supplementation and high-intensity interval training on neuromuscular fatigue and muscle function - Abbie E. Smith; Jordan R. Moon; Kristina L. Kendall; Jennifer L. Graef; Christopher M. Lockwood; Ashley A. Walter; Travis W. Beck; Joel T. Cramer; Jeffrey R. Stout (European Journal of Applied Physiology, 2009)